The Students’ English Vocabulary By Using Total Physical Response A Literature Study - Paulus Sainyakit (FKIP, Universitas Palangka Raya, 2024)
The vocabulary is needed to be mastered by the students in learning English. But in teaching vocabulary, we need to use an appropriate method. It is because with an inappropriate method, it would be difficult for students to master the vocabulary. The purpose of this research is to determine the Total Physical Response (TPR) can improve the students’ English vocabulary. This research uses a literature research. The sources are from journals, theses, and book. The results of the research show that an improvement in the students’ learning of every source. The average percentage of all researches used in this research on the students’ English vocabulary through Total Physical Response (TPR) starts from the lowest 40,33% to the highest 73,3% with a difference of 32,97%. Furthermore, the average percentage before using Total Physical Response (TPR) is 30,76%. After that, the results are improved when used TPR method. It improves to 56,81% for overall improvement. Based on that, it can be concluded that the Total Physical Response (TPR) method can improve the students’ English vocabulary.